2019
DOI: 10.3390/plants8110523
|View full text |Cite
|
Sign up to set email alerts
|

A World of Gorse: Persistence of Ulex europaeus in Managed Landscapes

Abstract: Gorse (Ulex europeus L.) is a woody legume and invasive woody weed that has been introduced to temperate pastoral landscapes worldwide. Despite the apparent cosmopolitan distribution of gorse across much of the temperate agroecological landscapes of the world, research and practice pertaining to the management of gorse has been largely constrained to single-treatments, regions, or timeframes. Gorse eradication has been widely attempted, with limited success. Using the PRISMA (preferred reporting items for syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 62 publications
1
36
0
1
Order By: Relevance
“…Currently, the Ulex europaeus, also known as gorse, is one of the world's most damaging invasive species, listed in the red list of the Global Invasive Species Database of the International Union for Conservation of Nature (UICN) [2]. Ulex europaeus is found practically all over the world and in all types of soil, due to its easy adaptation to changes in the environment, rapid growth, high reproductive output, propagule persistence, and low vulnerability to pests [3]. In Colombia, the Biological Resources Research Institute "Alexander Von Humboldt" has declared the Ulex europaeus as one of the invasive species with the greatest impact in the country [4], due to the negative effect that has been reported on the composition and structure of the vegetation, highlighting the invasion in the Andean region in the departments of Antioquia and Cundinamarca (e.g., in Bogotá it is found in ten of the fourteen wetlands declared by the district and in different parts of the city such as the eastern hills and rural areas) [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the Ulex europaeus, also known as gorse, is one of the world's most damaging invasive species, listed in the red list of the Global Invasive Species Database of the International Union for Conservation of Nature (UICN) [2]. Ulex europaeus is found practically all over the world and in all types of soil, due to its easy adaptation to changes in the environment, rapid growth, high reproductive output, propagule persistence, and low vulnerability to pests [3]. In Colombia, the Biological Resources Research Institute "Alexander Von Humboldt" has declared the Ulex europaeus as one of the invasive species with the greatest impact in the country [4], due to the negative effect that has been reported on the composition and structure of the vegetation, highlighting the invasion in the Andean region in the departments of Antioquia and Cundinamarca (e.g., in Bogotá it is found in ten of the fourteen wetlands declared by the district and in different parts of the city such as the eastern hills and rural areas) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Actions for the eradication of this shrub are based mainly on burning, revegetation with native species and manual and/or mechanical techniques with subsequent control of sprouts and seed banks [6]; however, the different processes that have been employed have not been effective due to the competitive characteristics of the plant and the impact generated on the ecosystems. In fact, the mechanical removal or destruction of Ulex europaeus can induce chronic soil erosion, compaction, and structural decline, which decreases prospects for sustainable land rehabilitation [3]. Thus, a large part of the research seeks to control this invasive plant, having found important results controlling it in the seedling phase through the formation of canopies of fast growing native species or with artificial shade [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Native to Western Europe, Ulex europaeus (Gorse) is an aggressive, evergreen and highly versatile shrub that is listed as one of the most invasive species in the world (Altamirano et al, 2016;Broadfield and McHenry, 2019). It has been introduced into several countries including Australia, Chile, New Zealand, Sri Lanka and the United States of America, where it was originally planted as a hedgerow, windbreak or cheap alternative to fodder within agricultural fields (Atlan and Udo, 2019;Broadfield and McHenry, 2019;Udo et al, 2017). Soon after its introduction, U. europaeus readily escaped regions where it was intentionally planted and has now become a ubiquitous presence in agricultural and native landscapes in over 50 countries (Clements et al,
…”
mentioning
confidence: 99%
“…In its non-native range, U. europaeus spread is fostered by a lack of native predation, high species reproductive output, a long vegetative period, prolonged seed longevity and rapid growth (Clements et al, 2001;Sixtus et al, 2013;Broadfield and McHenry, 2019;Kariyawasam and Ratnayake, 2019). Consequently, invasion by U. europaeus has led to a significant change in landscape dynamics arising from altered soil composition, increased soil acidity, the creation of shelter for pest species (feral cats, foxes and rabbits) via its dense thickets and a reduction in species richness (Gouldthorpe et al, 2006;Broadfield and McHenry, 2019). Ulex europaeus also significantly changes the frequency and intensity of fire through the landscape due to its high levels of natural oil and large accumulations of necromass (mostly dead branches and spines), which generate hotter than usual fires when ignited (Altamirano et al, 2016).…”
mentioning
confidence: 99%